Postmodern Grimaces of the Real - Žukauskaitė, Audronė (Problemos, 2003)
The article focuses on the concept of the Real and interprets it as a counterpoint to the discursive character of postmodern philosophy. Slavoj Žižek excerpts the concept of the Real from psychoanalysis of Jacques Lacan. Žižek insists that the Real as a traumatic kernel resists symbolization and forms the external limit to discourse. After the critical debates with Judith Butler and Charles Chepherdson on the ambivalent character of the Real, Žižek refined his position and defined the Real as the internal limit of the symbolical order. The article discusses the ambivalent character of the Real and its implications on sexual, ethical and political fields. The main question is does psychoanalysis really provide a 'third way' to the 'antinomy of postmodern reason', or is it, in an indirect way, 'the return of the Real'?
Keywords: postmodernism; deconstruction; psychoanalysis; representation; Imaginary Symbolic; the Real